2017
DOI: 10.14238/pi57.3.2017.164-70
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric index of mortality 3 score to predict mortality in a pediatric intensive care unit in Palembang, South Sumatera, Indonesia

Abstract: Background For critically ill patients in the pediatric intensive care unit (PICU), a scoring system is helpful for assessing the severity of morbidity and predicting the risk of mortality. The Pediatric Index of Mortality (PIM) 3 score consists of ten easy simple variables, so that the probability of death can be assessed prior to undergoing advanced therapies. The PIM 3 score in inexpensive and comprised of routine laboratory variables performed in PICU patients. In Indonesia, studies to validate the PIM 3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
(15 reference statements)
2
11
1
3
Order By: Relevance
“…Patients who were mechanically ventilated had more than two times increased hazard of death. This is in line with the findings of studies [33,34]. This might be due to the fact that patients who need mechanical ventilation are in advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Patients who were mechanically ventilated had more than two times increased hazard of death. This is in line with the findings of studies [33,34]. This might be due to the fact that patients who need mechanical ventilation are in advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…In Roshani et al study, cardiovascular involvement was the most common and in Sankar et al study, sepsis and malignancy in Destiana et al study done in Indonesia. 21,18,11 The mean predicted death rate was found to be statistically significant with the outcome as with other studies mentioned. 18,20 In another Indian study by Roshani et al study, in Mumbai tertiary care centre showed poor calibration with GOF p=0.028.…”
Section: Resultssupporting
confidence: 78%
“…The performance of this new model is yet to be assessed in Argentina. Similarly, literature related to validations of the score in populations different from the ones it was generated in is scarce (15–17).…”
mentioning
confidence: 99%